Two new water mite species of the Sperchon tridentatus-group from Asia (Acari, Hydrachnidia, Sperchontidae) - Tuzovskij, Petr V. (Zootaxa, 2021)
In the present study a description of two new species of the Sperchon tridentatus-group from Asia is presented. An identification key is given for the known species of the group.